Eosinophil‐derived exosomes contribute to asthma remodelling by activating structural lung cells. Issue 9 (8th March 2018) - Cañas, J. A.; Sastre, B.; Rodrigo‐Muñoz, J. M.; Fernández‐Nieto, M.; Barranco, P.; Quirce, S.; Sastre, J.; del Pozo, V.
Summary: Background: Eosinophils, a central factor in asthma pathogenesis, have the ability to secrete exosomes. However, the precise role played by exosomes in the biological processes leading up to asthma has not been fully defined. Objective: We hypothesized that exosomes released by eosinophils contribute to asthma pathogenesis by activating structural lung cells. Methods: Eosinophils from asthmatic patients and healthy volunteers were purified from peripheral blood, and exosomes were isolated from eosinophils of asthmatic and healthy individuals. All experiments were performed with eosinophil‐derived exosomes from healthy and asthmatic subjects. Epithelial damage was evaluated using primary small airway epithelial cell lines through 2 types of apoptosis assays, that is, flow cytometry and TUNEL assay with confocal microscopy. Additionally, the epithelial repair was analysed by performing wound healing assays with epithelial cells. Functional studies such as proliferation and inhibition‐proliferation assays were carried out in primary bronchial smooth muscle cell lines. Also, gene expression analysis of pro‐inflammatory molecules was evaluated by real‐time PCR on epithelial and muscle cells. Lastly, protein expression of epithelial and muscle cell signalling factors was estimated by Western blot. Results: Asthmatic eosinophil‐derived exosomes induced an increase in epithelial cell apoptosis at 24 hour and 48 hour, impeding wound closure. In addition, muscle cell proliferation was increased at 72 hours after exosome addition and was linked with higher phosphorylation of ERK1/2. We also found higher expression of several genes when both cell types were cultured in the presence of exosomes from asthmatics: CCR3 and VEGFA in muscle cells, and CCL26, TNF and POSTN in epithelial cells. Healthy eosinophil‐derived exosomes did not exert any effect over these cell types. Conclusions and Clinical Relevance: Eosinophil‐derived exosomes from asthmatic patients participate actively in the development of the pathological features of asthma via structural lung cells.